Exploring Diaspora Identities and Media Consumption among Indian Immigrants in the United States - Kumar, Rajiv; Fernandes, Muriel; Goswami, Vandana (Stallion Journal for Multidisciplinary Associated Research Studies, 2023)
This study delves into the experiences of Asian Indian immigrants residing in the United States and explores the intricate relationship between diasporic identities and media consumption. Grounded in the framework of cultural proximity, social identity theories, and the uses and gratifications perspective, the research investigates the viewership preferences and motivations of Asian Indian immigrants towards Indian television programming. Despite their extensive time living abroad, these immigrants actively choose ethnic programming, specifically Indian television accessible through satellite dishes, as a means to reinforce their ethnic identity, stay informed about India, and nurture a sense of connection to their cultural roots. By providing post-2014 insights into the dynamics of Asian Indian social identity, television consumption patterns, and the uses and gratifications derived from ethnic media, this study contributes to a deeper understanding of how diasporic individuals actively engage with media content to fulfill their needs for cultural preservation, reaffirmation of identity, and a continued link with their country of origin. The findings have implications for media organizations aiming to cater to diverse audiences and for scholars examining the interplay between media consumption and diasporic identities within an ever-evolving media landscape.